Do registered nurses have the tools to appropriately assess student nurses in the taking and interpretation of electrocardiograms?. (2nd November 2021) - Kirk, Mary; Wright, Christine
Abstract : The Nursing and Midwifery Council highlights that, at the point of qualifying, registered nurses should be able to undertake routine investigations, interpret and share the findings, as appropriate. This includes electrocardiograms. Registered nurses who act as practice assessors for student nurses need to have the skills themselves to be able to appropriately assess the student. This article investigates whether practice assessors hold the appropriate knowledge and skills to be able to undertake assessments. The understanding of the terminology 'interpreting findings' can be seen in different ways and this could influence nurses' skills acquisition. At what point does a nurse not require supervision and is considered competent in the skill of taking an electrocardiogram and interpretation? There is no national standard in England to agree the level at which competence is achieved. Student training in practice may vary due to the placement experiences gained throughout their training. From reviewing the literature and standards, it is suggested that registered nurses have varying standards of skills when it comes to interpreting electrocardiograms, derived from their training both as a student and as a nurse. It may also be influenced by the Registered Nurses workplace setting and whether regular and specialist electrocardiogram analysis is required. There appears to be no published evidence/information into current training provision for electrocardiogram analysis within England within a student nurses core curriculum.